Anticancer drug screening: standardization of in vitro wound healing assay - Vitor M. Almeida; Maximino Alencar Bezerra Jr; Jéssica C. Nascimento; Lidia Maria F. Amorim (Sociedade Brasileira de Patologia Clínica, 2020)
ABSTRACT Introduction: Gliomas are characterized by rapid proliferation and aggressive invasion into normal surrounding brain tissue. In medical laboratories, the in vitro wound healing assay stands out as a simple, easy, inexpensive and affordable method to evaluate cell migration and proliferation. Objective: To standardize the in vitro wound healing assay using antimicrotubule drugs as positive controls. Methods: U87MG glioma cells were seeded at different densities and, after 24 h, the monolayer was scratched using different micropipette tip size to create a gap with no cells. The cells were then treated with colchicine and paclitaxel in culture medium with the presence or absence of fetal bovine serum. The wound was photographed with the aid of an inverted microscope and the wound area was measured using the Image J software. Results: Better defined edges scratches and monolayer with approximately 90% confluence were obtained at 1.5 and 2 x 105 cells/well density. The width and area of the scratch were, respectively, 948 pm/2.193221 mm2; 964 pm/2.266 mm2 and 1448 pm/3.221 mm2 to 10. 200 and 1000 pl micropipette tips. Colchicine inhibited wound closure by 12.6% or 3.4%, both in the presence or absence of serum; paclitaxel 2.4 and 6.7% respectively. Conclusion: Under standardized conditions, colchicine and paclitaxel proved to be efficient positive controls into the in vitro wound healing assay.